Lower leg muscle recovery takes at least 12 months for functional tests to recover after late reconstruction of the tibialis posterior tendon retinaculum. Issue 1 (17th January 2022) - Rips, Leho; Luik, Mihkel; Koovit, Tauno; Rahu, Madis
Abstract : Traumatic dislocation of the tibialis posterior tendon is an extremely rare injury with few reported cases. It is a complicated injury with high risk of misdiagnosis and mistreatment. MRI is the best tool for diagnosis. Surgical treatment has been reported to have a better outcome than conservative treatment. In the present case, a 23-year-old female athlete sustained a sports-related traumatic tibialis posterior tendon dislocation with retinaculum rupture. The patient underwent late reconstruction of the ruptured retinaculum followed by a personalised rehabilitation programme. Full recovery was achieved after 19 months according to European Foot and Ankle Society Score and Foot and Ankle Outcome Score. Lower leg muscle strength continued to improve until 6 months after surgery in isokinetic strength and physical performance tests.